Tumor cell cytoplasmic metallothionein expression associates with differential tumor immunogenicity and prognostic outcome in high-grade serous ovarian carcinoma - Mairinger, Elena; Wessolly, Michael; Buderath, Paul; Borchert, Sabrina; Henrich, Larissa; Mach, Pawel; Steinborn, Julia; Kimming, Rainer; Jasani, Bharat; Schmid, Kurt Werner; Bankfalvi, Agnes; Mairinger, Fabian Dominik (Frontiers in Oncology, 2023)
Background: The underlying mechanism of high T cell presence as a favorable prognostic factor in high grade serous ovarian carcinoma (HGSOC) is not understood yet. Besides immune cells, various cofactors are essential for immune processes. One of those are metallothioneins (MTs), metal-binding proteins comprising various isoforms. MTs play a role in tumor development and drug resistance. Moreover, MTs influence inflammatory processes by regulating zinc homeostasis. Especially T cell function and polarization are particularly susceptible to changes in zinc status. The aim of the present study was to investigate a possible role of metallothionein mediated immune response and its association with prognostic outcome in ovarian cancer. Methods: A retrospective study was conducted on a clinically well characterized cohort of 24 patients with HGSOC treated at the University Hospital of Essen. Gene expression patterns for anti-cancer immunogenicity-related targets were performed using the NanoString nCounter platform for digital gene expression analysis with the appurtenant PanCancer Immune Profiling panel, consisting of 770 targets as well as 30 reference genes. Tumor associated immunohistochemical MT protein expression was evaluated using a semi-quantitative four-tier IHC scoring. Results: MT immunoexpression was detected in 43% (10/23) of all HGSOC samples. MT immunoexpression levels showed a significant association to survival, leading to prolonged progression-free and overall survival in positively stained tumors. Furthermore, T cell receptor signaling gene signature showed a strong activation in MT positive tumors. Activated downstream signaling cascades resulting in elevated interferon gamma (IFNγ) expression with a shift in the balance between T helper cells (TH1 and TH2) could be observed in the MT positive subgroup. Also, a higher expression pattern of perforin and several granzymes could be detected, suggestive overall of acute, targeted anti-cancer immune response in MT positive samples. Conclusion: This is the first study combining broad, digital mRNA screening of anti-tumor immune-response associated genes and their relation to MT-I/II in ovarian cancer. MT overexpression is associated with molecular characteristics of an anti-cancer immune response and is a strong prognostic marker in ovarian HGSOC. The observed immune cell activation associated with tumor MT expression comprises but is not limited to T cells and NK cells.